Studi Kualitatif: Kegagalan Pemberian Air Susu Ibu (ASI) Eksklusif di Puskesmas Sidomulyo Kota Bengkulu - Bayu Wicaksono; Betty Yosephin Simanjuntak; Tetes Wahyu Witradharma (Jurnal Keperawatan, 2023)
Breastmilk is the best natural food for babies, but the phenomenon that occurs in society today is that exclusive breastfeeding is still low. Low levels of exclusive breastfeeding can be detrimental to babies, mothers, families and the nation, including the risk of bad health. Efforts are needed from mothers of toddlers and support from outside to achieve the success of exclusive breastfeeding. The aim of this research is to explore in depth the causes of failure to provide exclusive breastfeeding at the Sidomulyo Community Health Center, Bengkulu City. This research is qualitative research with a phenomenological approach. Data collection obtained through in-depth interviews. The main study was 6 mothers who failed to breastfeed exclusively. Supporting informants consisted of 6 husbands/families, 1 head of the Community Health Center, 1 health worker, 1 KIA officer and 2 posyandu cadres at the Sidomulyo Community Health Center, Bengkulu City. The instrument used was an open question questionnaire. This research identifies the reasons why mothers do not give exclusive breast milk, namely breast milk that is not flowing smoothly, so the mother takes her own initiative to give formula milk to her baby. Even though support from husband/family and health workers has been provided, the failure of exclusive breastfeeding is still not resolved. So, from the results of this research, it is hoped that mothers can face all obstacles while providing exclusive breastfeeding, accompanied by support from their husband/family and health workers in providing advice, direction, opinions or explaining the appropriate actions to be taken by the mother.